IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING POETRY THROUGH CONTEXTUAL TEACHING AND LEARNING MODEL IN YEAR X IPA-2 OF MAN 2 WEST ACEH ACADEMIC YEAR 2022-2023 - Rosmininur, Rosmininur; Asmanidar, Asmanidar; Marsita, Marsita (LUMBUNG AKSARA, 2022)
This study aimed to determine "the improvement of students’ achievement in writing poetry through Contextual Teaching and Learning Model in Year X IPA-1 of MAN 2 West Aceh Academic Year 2022-2023" class X IPA-1 research sample, totaling 25 students. This study used Classroom Action Research with the method of observation, data collection, testing, documentation and data analysis. This study used two cycles to find out the increase in the results of the ability to write poetry in Year X IPA-1 of MAN 2 West Aceh Academic Year 2022-2023. The results of this study indicated that the Contextual Teaching and Learning model can improve the learning outcomes of Year X IPA-1 of MAN 2 West Aceh. It could be seen from the results of learning in the pre-cycle, cycle I and II. As for student learning outcomes in the pre-cycle, it was only 8 students (32%) who completed the passing grades, in cycle I, it increased to 17 students (68%) who reached the passing grades, and in cycle II, it got 25 students (100%) reach the passing grade.